Perlindungan Data Pribadi dalam Penerbitan Sertipikat Tanah Elektronik di Kabupaten Buleleng - Soinbala, Amos; Wahyudi, Wahyudi (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
The implementation of land rights certificates in electronic form in Buleleng Regency marks substantial progress in the modernization of land administration, in order to improve efficiency and ease of access to services. However, this innovation raises fundamental problems related to the security of the personal data of the rights owner. Electronic certificates include sensitive spatial and juridical property information, thus creating a dilemma between the principle of transparency to ensure legal certainty and confidentiality obligations in accordance with Law No. 27 of 2022 concerning Personal Data Protection (PDP Law). This study applies a qualitative methodology with a normative-juridical approach to analyze the relevant regulatory framework. The findings of the study show that the implementation of the PDP Law in Buleleng Regency is still faced with substantial obstacles, which is reflected in the increase in incidents of personal data leaks that threaten the integrity of individual identities and erode public trust in the digital system. The implementation, which currently refers to the Ministerial Regulation of ATR/BPN No. 1 of 2021 and Article 15 of the ITE Law, requires comprehensive strengthening through more specific regulations such as the Ministerial Regulation of ATR/BPN No. 3 of 2023, which explicitly regulates data classification, access authorization, and technical security procedures to achieve an optimal balance between the principles of transparency and data privacy.